A report on the techniques developed for chronic implantation of electrodes in the albino rat brain - Bourgeois, A. E. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The purpose of this paper is to describe the technical procedures involved in the surgical implantation of electrodes in the brain of the albino rat. These procedures are designed to be performed in a small laboratory with limited funds and with relatively unsophisticated personnel. Discussions of the pre-operative, operative, and post-operative techniques are included. A discussion of suggested methods for the design and construction of the implantation electrodes is presented, and a partial list of supplies and their sources follows.